2014
DOI: 10.1016/j.jpainsymman.2013.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Typology of Perceived Family Functioning in an American Sample of Patients With Advanced Cancer

Abstract: Context Poor family functioning affects psychosocial adjustment and the occurrence of morbidity following bereavement in the context of a family’s coping with advanced cancer. Family functioning typologies assist with targeted family-centered assessment and intervention to offset these complications in the palliative care setting. Objectives Our objective was to identify the number and nature of potential types in an American palliative care patient sample. Methods Data from patients with advanced cancer (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
57
3
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 19 publications
6
57
3
2
Order By: Relevance
“…Three contextual variables associated with conflict that also were reported in recent studies include prior family conflict, 12 younger age, 12,26 and female gender. 26 Although there was no relationship between conflict and advance directives, conflict was associated with advance planning discussions. Recent evidence suggests that more highly functioning and emotionally supportive families are more likely to have such discussions.…”
Section: Discussionmentioning
confidence: 83%
“…Three contextual variables associated with conflict that also were reported in recent studies include prior family conflict, 12 younger age, 12,26 and female gender. 26 Although there was no relationship between conflict and advance directives, conflict was associated with advance planning discussions. Recent evidence suggests that more highly functioning and emotionally supportive families are more likely to have such discussions.…”
Section: Discussionmentioning
confidence: 83%
“…In a cross-sectional study of 191 patient-caregiver dyads, lower levels of cohesiveness (family members' involvement in the family), expressiveness (family members' willingness to express their emotions openly) and conflict resolution (family's ability to solve disagreements) predicted depressive symptoms in both lung cancer patients and their caregivers (13). Previous studies investigating family functioning have shown that cohesiveness is the primary indicator of well-functioning families types (13-17). However, little is known about the relationship between family function and caregiver burden and well-being.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to the FRI, the cluster solution is generated based on the 3 FRI subscales (cohesiveness, expressiveness, conflict resolution). Cluster analysis of the FRI has been conducted in American, Japanese and Australian samples (14, 16, 17). The number of components generated from the cluster solutions varies from a 3 cluster solution (16) to a 5 cluster solution (12, 14, 17).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations